2021
DOI: 10.1371/journal.pone.0250241
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ attitude towards webinars and online education amid COVID-19 pandemic: When less is more

Abstract: Background Since the declaration of COVID-19 as a pandemic, all scientific medical activities were shifted to an online format, in the form of webinars, to maintain continuing medical education (CME). We aimed to assess physicians’ attitude among different medical specialties towards this sudden and unexpected shift of traditional face-to-face meetings into webinars, and to suggest future recommendations. Methods We conducted a cross-sectional, internet-based survey study using a 25-item questionnaire, from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 28 publications
(34 reference statements)
1
63
0
3
Order By: Relevance
“…The disruption of conventional medical education across the world in the COVID-19 pandemic has led to the use of webinars to maintain teaching and learning. In a study, the use of webinars in 2020 compared to the same period in 2019 was reported to increase by more than 300% (24).…”
Section: Discussionmentioning
confidence: 99%
“…The disruption of conventional medical education across the world in the COVID-19 pandemic has led to the use of webinars to maintain teaching and learning. In a study, the use of webinars in 2020 compared to the same period in 2019 was reported to increase by more than 300% (24).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, using an online educational model also helps reach a greater number of students and gives them access to the same kinds of resources, which offers a robust learning experience and more equal field of opportunities that these students may otherwise not have been able to access [ 18 , 19 ]. This is shown in other virtual education models that have been implemented in interdisciplinary fields in Egyptian medical schools.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, employing a multidisciplinary approach to radiology education at the medical student level can successfully be done virtually, both in response to the COVID-19 pandemic as well as to the changing fabric of medicine, with telehealth becoming more popular [ 18 , 23 ]. Online medical education can reach a wider range of students and their learning can be adequately assessed with a combination of live discussion sessions and testing methods [ 19 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Medical schools and institutions also faced the necessity for a significant increase in online learning. While this was initially well perceived by physicians and healthcare personal in general, physicians felt overwhelmed by the increased amount of offers and frequency of invitations [ 5 , 6 ]. A study from India examining the barriers in using E-learning methods for medical education suggests that Internet and utility infrastructure are major problems in accessing E-learning [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was complementary to the ILAE curriculum and had the objective of improving knowledge, understanding and application of current and upcoming scientific research in epilepsy related to COVID 19 and relevant for HCPs active in epilepsy. Through a highly interactive approach, including case-based learning, integrated tests and different digital formats, the project aimed to counteract the “digital fatigue” that has been identified in the literature [ 5 ]. Our review revealed that current literature about education under COVID-19 is largely focused on the evaluation of single or distinct series of single interventions.…”
Section: Introductionmentioning
confidence: 99%